Influencia del proyecto educativo institucional en la formación de pensamiento crítico en adolescentes de 11° de una institución educativa en la ciudad de Cartago - Valle del Cauca (2020)
The purpose of this work is to try to describe what influence the PEI of an institution has on the formation of critical thinking in adolescents; The research is of a qualitative nature and from a social-critical approach, since it is a social context, it trains citizens, therefore it is a tool that is socially offered and must concern everyone, since teaching to think must be a main objective of any educational institution; the design is phenomenological, as it focuses on the subjective individual experiences of the participants. The work unit for this research consists of 3 16-year-old adolescents: two women and one man; They are 11th grade students of the public institution. As an instrument, characterization cards and the semi-structured interview were used to access the data and the narrative of the students, in order to proceed to the analysis and discussion of the information and draw the final conclusions.